(untitled) (Texas Journal of Medical Science, 2024)
The article presents an analysis of the nutrient composition of the diet of student-athletes. 22 students of different levels of sports qualifications took part in the study. Analysis of the survey showed a problem caused by the fact that among respondents there is an understanding of the biochemical essence of sports nutrition (in theory), but it is rarely used by studentathletes in practice